Growth trajectories of HIV exposed and HIV unexposed infants: a prospective study in Gweru, Zimbabwe - Mabaya, Lucy; Matarira, Hilda Tendisa; Tanyanyiwa, Donald Moshen; Musarurwa, Cuthbert; Mukwembi, Johannes (SAGE Publications, 2021)
Background: With the increasing HIV seroprevalence among women of childbearing age in sub-Saharan Africa, limited data on growth outcomes of HIV exposed infants under current policies of universal maternal antiretroviral therapy exist.